Maleic Anhydride Modified Dicyclopentadiene Resin for Improving Wet Skid Resistance of Silica Filled SSBR/BR Composites - Ruoming Huang (Applied Sciences, 2020)
As commercial rubber in tires, silica-filled solution-polymerized styrene-butadiene rubber/butadiene rubber (SSBR/BR) compounds exhibited preferable wet skid resistance (WSR) properties, which could be further enhanced by the incorporation of some oligomeric resins. However, the untreated dicyclopentadiene (DCPD) resin shows a slight improvement in wet friction even if the good compatibility between DCPD and SBR owing to their common cyclic structures. For this problem to be addressed, we aimed to enhance its resin-silica interaction by reaction with maleic anhydride (MAH). In detail, the effect of MAH content on WSR, curing characteristics, physical-mechanical properties of the silica-filled SSBR/BR composites was investigated. When the MAH content is 4 wt% in the modified DCPD resin, the maximum enhancement of about 15% in tan δ values at 0 ℃, as well as that of 17% in British pendulum skidding tester (BPST) index is obtained, indicating a desirable improvement in WSR. In addition of these two commonly used methods, water contact angles of the vulcanizates increase gradually with increasing MAH content, further confirming the remarkable performance of modified DCPD resin in WSR.